FAKTOR SOSIAL BUDAYA DAN ATURAN PERUNDANGAN - Musyfikah Ilyas (Fakultas Syariah dan Hukum Islam Institut Agama Islam Negeri (IAIN) Parepare, 2015)
There are two main issues discussed in this study. They were the dynamics of socio-cultural factors before the birth of the legislation and the effects of both of these factors to the public after enactment. The focus of the regulations rules in this study is the law of marriage. Based on the formal judicial approach, there is a very strong influence on society change after the birth of some the regulations rules related to marriages registration, polygamy, marriage age limit, divorce before the court, and the status of children in marriage. The changes are more affected by socio-cultural factors.